Revolusi Ruang Hidup dengan Teknologi Smart Home - Armiwaty M; Raeny Tenriola Idrus; Noor Fadilah Romadhani (Universitas Negeri Makassar, 2023)
In recent years, there has been a significant increase in the adoption of smart home technology. From voice assistants like Amazon’s Alexa and Google Home to smart thermostats and security systems. Smart home technology is becoming more and more commonly used by modern society. The aim of this research is a review of smart home technology that can revolutionize our living space. The results of the review conclude that smart home is a technology that is increasingly being used. This smart home has many advantages, but also has some disadvantages that need to be considered. The development of this smart home is an interesting and potentially revolutionary way of living and how we interact with living space.